Developing Tourism Management Materials For EFL Learners Based on Local Needs - Moh. Farid Maftuh; Jannatul Laily Noviabahari; Rizka Maulina Wulandari (FKIP, Universitas Palangka Raya, 2023)
The teaching material design of Tourism Management should meet the vocational students' needs and be relevant to the workplace milieu. A few coursebooks have recently been offered to fulfill the student's needs. Some books that are usually used are about tourism management materials in general. It needs to meet the student's needs. This study aims to describe the process of developing English Materials for Tourism Management courses and how the development of English materials for Tourism Management courses can help students learn Tourism Management. The method used was Research and Development. There were four steps: Defining, Designing, developing, and disseminating. The finding showed that developing materials follows four steps: define, design, design, and disseminate. In Define showed that EFL learners and lecturers need relevant teaching-learning materials that can instantly be applied in the teaching-learning process. In Desing, steps showed that the result of the design stage is a Tourism Management handout based on problem-based learning. The result of this book design is that it contains ten chapters and 110 pages. In Develop steps is the validity test. The last step is Dissemination; the materials are shared with the EFL Learners and lecturers who taught tourism management classes as a reference. This study had two implications; first, Developing this textbook would improve the lecturer's role in the Tourism Management classroom as a facilitator, motivator, and manager. Second, implementing this textbook into the teaching-learning process in Tourism Management classes can improve students' motivation.